Supply of medicines by humanitarian organizations in war conditions - Musa, Mexhit (Technium BioChemMed, 2022)
Natural and war disasters lead to stagnation in economic, social and, yes, health development. During the war, the own production of medicines was significantly reduced or even completely stopped due to the destruction of factories, the impossibility of securing raw materials for the production of medicines, and due to the difficulty of importing, transporting and distributing medicines. Even during the war, chronic non-communicable diseases that require daily intake of several groups of drugs are common, the therapy is long-term, and it is necessary to provide a large amount of drugs for these patients. (Abrams J. Nitroglycerin and long-acting nitrates. N Engl J Med 1980; 302:1234). Under these conditions, humanitarian organizations are often the only ones who are able to secure and deliver medicines to certain war-affected areas, which was the case in Bosnia and Herzegovina. Frequent scientific and non-scientific discussions indicate that the medicines donated through humanitarian organizations are outdated and inadequate in relation to the needs of the population. In my research related to the humanitarian organization "Igasa", which included a clinic and a pharmacy and provided help through diagnostics and therapy mainly to chronic internal medicine patients, and for the period from January 2, 1994 to December 31, 1995. I found the following data: 12,839 patients with (CVD, GIO and diabetes mellitus) sought help in this clinic and pharmacy. Of these, 68.00% had CVD, 17.00% GIO and 15.00% diabetes mellitus. Of the total number of patients, 59.00% were women, and 41.00% were men. A significant difference was recorded in the number of patients with CVD according to GIO and diabetes mellitus (p = < 0.001). The highest consumption of drugs was for the treatment of CVD patients (75.00%), while the number of drugs for the treatment of GIO and diabetes mellitus amounted to (25.00%) of the total drug consumption, this is shown by a significant difference (p = < 0.001). The total monetary value of medicines issued in the period 1994 and 1995 in the humanitarian pharmacy "Igasa" is 369,816.28 KM. There was a significant difference in the consumption of medicines as well as the difference in the monetary value of the dispensed medicines between the humanitarian pharmacy "Igasa" and the civilian pharmacy "Bascarsija".